Studies on the effect of various priming treatments for quality seed production in sesame cv. VRI 1: SEED INVIGORATION STUDY IN SESAME - M PRAKASH; G SATHIYA NARAYANAN; B S R V SAI PRADEEP KUMAR (Journal of Oilseeds Research, 2019)
Sesame (Sesamum indicum L.; Pedaliaceae) is one of the oldest oil seed crops grown widely in tropical and subtropical areas for its edible oil, proteins, vitamins, and amino acids. Quality seeds along with other improved package of practices play a vital role in improving productivity of crops under rainfed condition. Different techniques are used to enhance vigour of the plants and crop yield of which, seed priming is the simple and suitable technique to increase germination, emergence and establishment. Hence, the present investigation was carried out to study the effect of various seed priming treatments on quality seed production in sesame cv. VRI 1. The seeds of sesame were given with various priming treatments i.e., priming with GA3 @ 100 ppm, IAA @ 100 ppm, MnSO4 @ 0.5, FeSO4 @ 0.5%, KCl @ 0.5%, prosopis leaf extract @ 2%, pungam leaf extract @ 2%, arappu leaf extract @ 2%, tamarind leaf extract @ 2% and nochi leaf extract @ 2%. Seeds treated with just water acted as control. All the treated seeds were evaluated for the initial quality characteristics and field performance. Among the treatments, it was found that prosopis leaf extract treatment @ 2% registered higher values for initial seed qualities. In field evaluation also, prosopis leaf extract treatment @ 2% recorded higher growth, physiological and yield parameters in sesame cv. VRI 1.